2020
DOI: 10.1101/2020.07.01.20143958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genome epidemiological study of SARS-CoV-2 introduction into Japan

Abstract: Background: After the first case of COVID-19 in Japan on 15 January 2020, multiple nationwide COVID-19 clusters were identified by the end of February. The Japanese government focused on mitigating emerging COVID-19 clusters by conducting active nationwide epidemiological surveillance. However, an increasing number of cases appeared until early April, many with unclear infection routes exhibiting no recent history of travel outside Japan. We aimed to evaluate the severe acute respiratory syndrome coro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…High-quality genome sequences were obtained from 49 of the 89 patients who were enrolled in the clinical trial at hospital sites located across Japan. A previous genome surveillance study suggested that two introductions of SARS-CoV-2 to Japan occurred, the first one between January and February from China and the second one since March from Europe and North America [1]. The clades identified in our trial mirrored this trend.…”
Section: Sars-cov-2 Clade Representationsupporting
confidence: 77%
See 1 more Smart Citation
“…High-quality genome sequences were obtained from 49 of the 89 patients who were enrolled in the clinical trial at hospital sites located across Japan. A previous genome surveillance study suggested that two introductions of SARS-CoV-2 to Japan occurred, the first one between January and February from China and the second one since March from Europe and North America [1]. The clades identified in our trial mirrored this trend.…”
Section: Sars-cov-2 Clade Representationsupporting
confidence: 77%
“…Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, has claimed nearly three million lives worldwide. Japan has been affected since the relatively early stage of the pandemic, with initial influx of strains from China during the lunar new year followed by strains from Europe over the spring of 2020 [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is quite intriguing that D614G_KR is dominant despite the fact that comparable numbers of D614G and D614G_Q57H strains were introduced into Japan. For unknown reasons, strains other than D614G_KR are short lived in Japan( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…On January 6, 2021, the NIID detected a new emerging strain (P.1 lineage) of SARS-CoV-2 at airport quarantine in four travelers who arrived from Brazil on 2 nd January 2021 [30-32] (Table 1). Subsequently, almost of P.1 lineage discovered in Manaus in Brazil and gradually spread worldwide [10, 11].…”
Section: Discussionmentioning
confidence: 99%